Competition between H2O and (H2O)2 reactions with CH2OO/CH3CHOO. Issue 6 (21st January 2016) - Lin, Liang-Chun; Chang, Hung-Tzu; Chang, Chien-Hsun; Chao, Wen; Smith, Mica C.; Chang, Chun-Hung; Jr-Min Lin, Jim; Takahashi, Kaito
Abstract : We calculated the bimolecular rate coefficients for the CH2 OO/CH3 CHOO reactions with H2 O/(H2 O)2 . Abstract : In this study, we performed ab initio calculations and obtained the bimolecular rate coefficients for the CH2 OO/CH3 CHOO reactions with H2 O/(H2 O)2 . The energies were calculated with QCISD(T)/CBS//B3LYP/6-311+G(2d, 2p) and the partition functions were estimated with anharmonic vibrational corrections by using the second order perturbation theory. Furthermore, we directly measured the rate of the CH2 OO reaction with water vapor at high temperatures (348 and 358 K) to reveal the contribution of the water monomer in the CH2 OO decay kinetics. We found that the theoretical rate coefficients reproduce the experimental results of CH2 OO for a wide range of temperatures. For anti - ( syn -) CH3 CHOO, we obtained theoretical rate coefficients of 1.60 × 10 −11 (2.56 × 10 −14 ) and 3.40 × 10 −14 (1.98 × 10 −19 ) cm 3 s −1 for water dimer and monomer reactions at room temperature. From the detailed analysis of the quantum chemistry and approximations for the thermochemistry calculations, we conclude that our calculated values would be within a factor of 3 of the correct values. Furthermore, at [H2 O] = 1 × 10 17 to 5 × 10 17 cm −3, we estimate that the effective first-order rate coefficients for CH2 OO, anti - and syn -CH3 CHOO reactions with water vapor will be ∼10 3, ∼10 4, and ∼10 1 s −1, respectively. Thereby, for Criegee intermediates with a hydrogen atom on the same side as the terminal oxygen atom, the reaction with water vapor will likely dominate the removal processes of these CIs in the atmosphere.